1057 Distinguishing Between Kleine-Levin Syndrome and Bipolar Disorder, a Delayed Diagnosis of a Rare Sleep Disorder. (12th April 2019) - Al-Sharif, Hussam Z; Thomas, Aaron P
Abstract: Introduction: Kleine-Levin syndrome (KLS) is a rare sleep disorder with a prevalence of one to two cases per one million population. The disease is characterized by episodic severe hypersomnia in addition to cognitive, behavioral, and psychological disturbances. Symptoms of KLS can mimic psychiatric disorders. Diagnosis of KLS in the setting of an existing psychiatric disorder can be challenging. We present a case of KLS in a patient with bipolar disorder. Report of Case: A 32-year-old male with bipolar I disorder, post-traumatic stress disorder, and moderate obstructive sleep apnea with an Apnea Hypopnea Index (AHI) of 21/hour presented with recurrent episodes of daytime sleepiness. Hypersomnia episodes began at age 17 years, lasted between one to six weeks, and occurred with a frequency of two episodes per year. The patient reported an increase to 12–14 hours of sleep per day. These episodes were associated with an increased calorie intake, derealization (i.e. the patient felt like he was walking outside of his body), apathy, hypersexuality, and mental slowness. These episodes recurred despite excellent adherence to continuous positive airway pressure. The patient denied restless leg symptoms, sleep paralysis, hypnogogic hallucinations, and cataplexy. His bipolar disorder was well controlled on risperidone and lamotrigine without any recent mood or medication changes. The hypersomnia episodes differed from his manic episodes, which were associated with short sleep duration and minimal daytime sleepiness, and from his depressive episodes, which were characterized by depressed mood and suicidal ideation. Between the hypersomnia episodes, the patient exhibited normal alertness, cognitive function, and behavior. The physical exam was notable for a body mass index of 39. Results including hemoglobin, thyroid stimulating hormone, vitamin D, renal panel, hepatic panel, urine toxicology, and brain magnetic resonance imaging were normal. KLS was diagnosed based on the constellation of symptoms meeting the International Classification of Sleep Disorders-3 criteria. Conclusion: KLS is a rare sleep disorder. Other psychiatric, neurologic and sleep disorders share some similar symptoms. Diagnosis of KLS in the setting of existing psychiatric disorders is challenging, however KLS can be distinguished by its clinical features and should be considered even in the presence of such disorders.